Infecção pelo vírus da diarreia viral bovina em vacas gestantes abatidas no Estado de São Paulo-Brasil - Oliveira, M. C. [UNESP]; Alexandrino, B. [UNESP]; Borges, L. A. [UNESP]; Medeiros, A. S R [UNESP]; Affonso, I. B. [UNESP]; Dias, F. C.; Samara, S. I. [UNESP] (My University, 2012)
The most important pathogens in the bovine livestock nowadays in the virus of the viral diarrhea mainly for triggered clinical manifestations related to the reproductive sphere. The infection in pregnant females, may result in abortions, embryonic resorptions, fetal mummification, birth of weak and malformation of the cattle. Moreover, their birth with persistently infected and immunotolerant virus, which the source of infection and dissemination of their disease. Nowadays, the complexity of the diagnosis and consequently its pathogenesis are tilted in the genotypic differences agent. So, this study aimed to verify the occurrence of the BVDV-1 (SINGER) and BVDV-2 (VS-253) genotypes in cows and their respective fetuses, slaughtered in an abattoir in the State of Sao Paulo. Through blood serum, using virus neutralization technique. All in all, 52,51% (115/219) of the cows which were tested reacted, but no fetus (0/219) reacted, to its virus neutralization. Through this cross-examination we observed that 42% (92/219) of cows reacted for both BVDV-1 and BVDV-2. Furthermore 4,10% (9/219) of them reacted only to the genotype BVDV-1 and 6,39% (14/219) responded only to the genotype 2 of BVDV. Therefore it was noticed that both strains are widespread in the regions studied, which justifies the use of different antigens to avoid false-negative diagnosis. Finally antibodies showed no fetus or fetal abnormalities, it is already developed and can be considered immunocompetent, independent child born to a reagent.
The infection through virus of the bovine viral diarrhea in pregnant cows, slaughtered in the State of Sao Paulo, Brazil
Keywords: Bovine; Bovine viral diarrhea virus (BVDV); Virus neutralization; Bos; Bovinae; Bovine viral diarrhea virus 1; Bovine viral diarrhea virus 2